Inside Front Cover. Issue 3 (March 2016) - Durán, América Paz; Inger, Richard; Cantú‐Salazar, Lisette; Gaston, Kevin J.
Abstract : The cover image, by America Paz Duran et al., is based on the Biodiversity Research Species richness representation within protected areas is associated with multiple interacting spatial features, DOI:10.1111/ddi.12404 .